Security and Privacy Challenges in The Internet of Medical Things (IOMT): A Comprehensive Review - Farooqi, Shaista Ashraf; Zafar, Fatima (2024)
As technology continues to advance at a rapid pace, the Internet of Things (IoT) has emerged as a transformative force in our daily lives, with intelligent devices seamlessly integrated into our homes and workplaces, revolutionizing the way we interact with the world. However, as the IoT has expanded to include medical devices, concerns have arisen over the security of personal information and the potential for data breaches. This paper takes a closer look at the privacy and security challenges that arise with the Internet of Medical Things, exploring potential solutions to safeguard sensitive information from unauthorized access and misuse. The motivation of this review is to provide valuable insights into IoMT's context. It aims to benefit healthcare professionals, data scientists, and technologists. The study covers AI models that maintain patient privacy while enhancing patient care, nuanced techniques for data scientists, and inspiration for building secure and effective IoMT solutions for technologists. Ultimately, it seeks to empower and inform stakeholders in shaping the future of healthcare through IoMT technologies.